PERBANDINGAN EFEKTIVITAS PIJAT REFLEKSI KAKI DAN AKUPRESUR TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI - Melisa, Santi; Karim, Darwin; Elita, Veny (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Hypertension is a risk factor of cardiovascular disease and therefore the management to avoid further complications is required. Non pharmacological management can be applied to hypertension is foot reflection massage and acupressure. The purpose of this research was to compare the effectiveness of foot reflection massage and acupressure on blood pressure in patients with hypertension. The design of this research is quasy experimental design with pre test and post test with two comparative study. The sample was 34 respondents who were devided into 17 as foot reflection massage group and 17 as acupressure group at Puskesmas Rejosari Pekanbaru. The instruments of this study were omron digital sphygmomanometer and observation sheet. The data used systolic and diastolic blood pressure for 3 days pre-test and post-test. The analyses used were univariate analysis to determine frequency distribution and bivariate analysis by using Dependent T-test, Wilcoxon, Independent T-test, and Mann Whitney. The reducing mean in systolic and diastolic blood pressure was 6,08 mmHg and 4,46 mmHg in the foot reflection massage group and 8,91 mmHg and 6,52 mmHg in the acupressure group. The result of bivariate analysis showed p value of systole blood pressure = 0,531 and diastole blood pressure = 0,904 > Î± (0,05), it can be concluded that there is no significant difference of systolic and diastolic blood pressure between the two therapies. Based on these results, the researcher suggest for health care provider to promote the program of foot reflection massage or acupressure to stabilize blood pressure for patients with hypertension. Keywords : Acupressure, blood pressure, foot reflection massage, hypertension